Association between Neutrophil/lymphocyte ratio and suitable shocks in heart failure patients with implantable cardiac defibrillator - Yucel, H.; Beton, O.; Zorlu, A.; Dogdu, O.; Turgut, O. O.; Yilmaz, M. B. (Wiley-Blackwell, 2014)
[Abstract Not Available]